SCISOLA: REAL-TIME MOMENT TENSOR MONITORING FOR SEISCOMP3 - Triantafyllis, N.; Sokos, E.; Ilias, A. (Bulletin of the Geological Society of Greece, 2016)
Automatic Moment Tensor (MT) calculation is exceptionally valuable in many realtime seismological applications, such as shake map generation or tsunami warning. Scisola, a new software for automatic MT retrieval, has been recently developed. This software binds the extensively used ISOLA MT inversion code with the widely known real-time seismological processing tool, SeisComP3. Automatic MT calculation is achieved by passing the event location information, the waveforms and the station meta-data produced by SeisComP3 to ISOLA. Scisola has been written in Python, many powerful libraries were used and significantly reduced the MT computation time by calculating the Green’s functions and the centroid position/time grid search in parallel mode. This tool provides a graphical user interface for easy solution overview of the extended graphical output and a quick revision of the corresponding solution; a database for storing the results and an extensive configuration customized to the user’s preferences. Apart from the real-time MT approach, scisola is capable of running in offline mode mostly for testing or playback purposes. Lately, a scisola plug-in was completed for real-time MT monitoring by automatically updating a Web page with the latest MT calculations. The code’s performance was compared to manual MT solutions and proved to be satisfying.